Repeated subglacial jökulhlaups in northeastern Greenland revealed by CryoSat - Laurence Gray; David Burgess; Luke Copland; Christine Dow; Xavier Fettweis; David Fisher; Will Kochtitzky; Wesley van Wychen; James Zheng (Journal of Glaciology)
Surface height changes above three previously undetected subglacial lakes in northeastern Greenland are documented using CryoSat, DEMs and ICESat-2. Between 7 February and 6 March 2012, the central ice region (22.6 km2) above the largest lake dropped by ~37 m followed by a further drop of 12 m in the following 29 days. This implies a subglacial water outflow, or jökulhlaup, of at least 1 km3 at rates of hundreds of cubic meters per second. A comparable outflow occurred again between 23 July and 15 September 2019, with smaller outflows in the fall of 2014 and 2016. In contrast, a second smaller subglacial lake at a higher elevation had two subglacial outbursts of ~0.3 km3 in 2012 and 2019 but the lake filling was gradual and not strongly seasonal or episodic. Water remained in both lakes after the outflows but this may not be the case for the third smallest and lowest subglacial lake. While there appears to be some hydrological link between the three lakes, the flux of water moving under the ice in this area appears to be larger than would be expected from local summer melt. However, the source of the excess water remains uncertain.